2017
DOI: 10.1111/cei.12950
|View full text |Cite
|
Sign up to set email alerts
|

UK NEQAS survey of allergen component testing across the United Kingdom and other European countries

Abstract: SummaryThe clinical utility of molecular diagnostic approaches in allergy investigation is increasingly being recognized to play a significant role in the management of allergic patients. Determining the sensitisation pattern, which is best achieved through the use of component resolved diagnostics (CRD), allows effective risk stratification, appropriate treatment and patient selection for immunotherapy.In order to assess the diagnostic service provisions for in vitro allergy testing across Europe, a survey wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Following a recent survey into the use of CRD within allergy testing across the UK and Europe, 1 it was apparent that use of CRD was becoming increasingly incorporated into routine diagnostics. Its clinical utility however was potentially being compromised due to limited understanding and interpretive guidance for requesting clinicians.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Following a recent survey into the use of CRD within allergy testing across the UK and Europe, 1 it was apparent that use of CRD was becoming increasingly incorporated into routine diagnostics. Its clinical utility however was potentially being compromised due to limited understanding and interpretive guidance for requesting clinicians.…”
Section: Introductionmentioning
confidence: 99%
“…Following a recent survey into the use of CRD within allergy testing across the UK and Europe (1), it was apparent that use of CRD was becoming increasingly incorporated into routine diagnostics; however its clinical utility was potentially being compromised due to limited understanding and interpretive guidance for requesting clinicians. With wider implementation, the immunology laboratory must consider the practical aspects for CRD, both methodological and interpretative, prior to the introduction of these specialised tests.…”
Section: Introductionmentioning
confidence: 99%
“…Conventional allergy tests such as SPT and slgE to allergen extracts are unable to differentiate sensitization from clinical allergy, resulting in overdiagnosis. More advanced antigenbased tests such as component-resolved diagnostics (CRD) may lead to a more accurate diagnosis and selection of therapeutic intervention,90,91 and becoming increasingly incorporated into routine diagnostics 92. A recent systemic review suggested that sIgE The reports on passive sensitization strategies using the mast cell lines12 or mast cell precursors13 showed promising po-…”
mentioning
confidence: 99%